Optimization of the spray drying process for obtaining cape gooseberry powder: an innovative and promising functional food - Cortés, Misael; Hernández, Gustavo; Estrada, Eliana M. (Vitae, 2017)
Background: currently, functional foods are the type of foods of most interest to the modern consumer, due to the health benefits they provide. Objectives: Optimize the spray drying process to obtain cape gooseberry powder added with active compounds. Methods: A process of spray drying was carried out to obtain a powder from cape gooseberry suspensions added with vitamin C, iron, folic acid, isolated soy protein and dietary fiber. The drying process was optimized according to the characteristics of food formulations and operating conditions, obtaining a product with low hygroscopicity, high solubility and high levels of physiologically active compounds. Response surface methodology was used, considering a central composite design with four factors: maltodextrin (0-40%p/p), inlet air temperature (170-210°C), atomizer disc speed (16000-24000 rpm) and outlet air temperature (75-95°C). Results: The results showed a higher retention of vitamin C (69.7±0.7%), folic acid (90.9±1.8%) and iron (90.8±1.0%) with the food formulation containing a 24.4% of maltodextrin and the drying process defined by an atomizer disc speed of 19848 rpm and inlet and outlet air temperature of 194.2°C and 87.7°C, respectively. Conclusions: The spray drying process is an effective technology that provides added value to the fruit of cape gooseberry, allowing the incorporation and conservation of active compounds such as iron, folic acid and ascorbic acid.